Diabetic retinopathy and transcriptional regulation of a small molecular weight G-Protein, Rac1. (June 2016) - Kowluru, Renu A.; Mishra, Manish; Kumar, Binit
Abstract: In diabetic retinopathy, increased cytosolic reactive oxygen species, produced by NADPH oxidase (Nox), damage mitochondria, and this accelerates apoptosis of retinal capillary cells, resulting in the histopathology. Activation of Nox2 is mediated by a small molecular weight GTPase, Rac1, and retinal Rac1 is activated in diabetes. Our goal is to investigate the molecular mechanism responsible for transcriptional activation of Rac1 in the development of diabetic retinopathy. Using retinal microvessels, the site of histopathology associated with diabetic retinopathy, from streptozotocin-induced diabetic rats, we investigated the binding of the nuclear transcriptional factor- k B (NF- k B) at Rac1 promoter. Since activation of NF- k B is regulated by its acetylation-deacetylation, the role of acetylation in Rac1 transcription was confirmed in the retina from diabetic mice overexpressing a deacetylase, Sirtuin 1. Diabetes increased the binding of p65 subunit of NF- k B at the Rac1 promoter. Overexpression of Sirtuin 1 prevented hyper-acetylation of p65, decreased its binding at the Rac1 promoter and ameliorated Rac1-Nox2 mediated mitochondrial damage. Thus, in diabetes Rac1 transcriptional activation in the retina is mediated by acetylation of NF- k B, and modulation of acetylation during the early stages of diabetic retinopathy has potential to inhibit/retard its development. Highlights: Transcription of retinal Rac1 in diabetes is regulated by NF- k B. Hyperacetylation of NF- k B increases its binding at Rac1 promoter. Overexpression of deacetylase, Sirt1, prevents diabetes-induced increase in Rac1. Rac1, via Nox2-ROS, damages mitochondria, initiating a futile cycle of ROS. Regulation of Sirt1 should ameliorate development of diabetic retinopathy.